Software Packages for Econometrics: Financial Time Series Modeling - Liashenko, Olena; Kravets, Tetyana; Krytsun, Kateryna (Information and Communication Technologies in Education, Research, and Industrial Applications, 2018)
In the article the comparative analysis of most common among economists software packages R, EViews and Gretl in financial time series modeling is conducted. Advantages and disadvantages of each software are considered. Volatility is often used as a rough approximation to measuring of financial instruments risk. For the modeling of financial time series volatility Polish stock index WIG was chosen. For describing the volatility of financial time series econometric model of family GARCH is built by means of these packages.